Calculus: Early Transcendentals (2nd Edition)

Published by Pearson
ISBN 10: 0321947347
ISBN 13: 978-0-32194-734-5

Chapter 3 - Derivatives - 3.4 The Product and Quotient Rules - 3.4 Exercises - Page 160: 23


$f'(x) = \frac{1-x}{e^x}$

Work Step by Step

$f(x)=xe^{-x} = \frac{x}{e^x}$ Quotient Rule: $f'(x) = \frac{(1)(e^x)-(x)(e^x)}{e^{2x}} = \frac{e^x-xe^x}{e^{2x}} = \frac{1-x}{e^x}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.